Prevalence of Cannabis use among students at a public university in Bahia: comparison between repeated surveys - Ferreira de Sousa, Thiago; da Silva Ferreira, Mariana (O Mundo da Saúde, 2020)
The aim of this study was to compare the prevalence of Cannabis use between two repeated surveys among university students at a public higher education institution in Bahia. Two repeated surveys were carried out with university students from the same institution in the years 2012 and 2014. This study investigated Cannabis use during the 30 days prior to the survey. The comparisons between the surveys were performed using the Chi-squared test and Fisher’s exact test. The participation was 1,085 and 1,041 university students in the years 2012 and 2014, respectively. The prevalence of Cannabis use, one or more times in the previous 30 days, increased between surveys from 2.4% to 5.8%. This increase was observed among women, university students aged 21 to 23 years and aged 24 and over, students with a father who had higher education level and a mother with a high school education; moreover, there was an increase in consumption for university students with and without a partner, and between those who studied either during the day or night. There was also an increase in consumption among university students who did not smoke and those who reported excessive alcohol consumption. The university students who reported not playing team sports, stood out with the increase in consumption between surveys, going from 1.9% in 2012 to 5.9% in 2014. It can be concluded that there was an increase in the consumption of Cannabis use between two surveys, with an emphasis on the increase in different groups, such as women and university students who drank alcohol excessively and who did not play team sports.